(untitled) (Journal of the College of Basic Education, 2022)
Crimes of drug trafficking and psychotropic substances are among the most important problems presented and which have a bearing on the security of the Iraqi state because of their great and direct impact on the productive youth groups in particular and on the Iraqi society in all its groups in general, and this is what prompted the researcher to present a major problem, which was: Did it help Geographical, temporal and spatial variables in the growth and spread of crimes of drug trafficking and psychotropic substances in the Iraqi state? Through the study, it was found that the geographical variables have an effect on the growth and spread of crimes of drug trafficking and psychotropic substances, and then the direct impact of the power of the Iraqi state, as it works to destroy the social and economic fabric and violates the security and sovereignty of the Iraqi state, and from here emerged the importance of the topic, which is represented by the diversity of these crimes and the extent of their impact on security The internal and external public of the Iraqi state in general and society in particular, as it has spread in a dangerous and striking way.